Quilombola representations of the Dandara group of the Sussuarana community of Piripiri, Piauí, Brazil (Research, Society and Development, 2020)
This research portrays the history of Afro-descendant presence with an emphasis on women who represent the Dandara group in the Sussuarana quilombola community of Piripiri, Piauí, Brazil. We seek to know the theme through a history of how the Sussuarana quilombo and the female representation of the Dandara group emerged with the challenges of assuming leadership positions. The methodology used in this research, is the narrative method consisting of interviews with the representativeness of the group, field observations and analysis of written, audiovisual and bibliographic documents. Theoretical foundations were made related to gender and slavery, in order to understand how the quilombola woman's expressiveness took place in a patriarchal society, in search of autonomy, which will be discussed to the detriment of her struggles for better working conditions, given the racism in social spaces and machismo in the rural context.